Growth differentiation factor 15 at 1 month after an acute coronary syndrome is associated with increased risk of major bleeding - Lindholm, Daniel; Katus, Hugo (Journal of the American Heart Association, 2017)
Background: Growth differentiation factor‐15 (GDF‐15) is related to major bleeding when measured at initial presentation in patients with acute coronary syndromes (ACSs) treated with dual antiplatelet therapy. It is unknown whether follow‐up measurements provide additional information. The objective of this study was to investigate whether GDF‐15 measured 1 month after an ACS provides additional information beyond the baseline levels with regard to the risk of major bleeding. Methods and Results: GDF‐15 was measured at baseline and at 1 month after an ACS in 4049 patients included in the PLATelet inhibition and patient Outcomes (PLATO) trial. The association between 1‐month GDF‐15 level and non–coronary artery bypass grafting surgery‐related major bleeding was assessed by a multivariable Cox model, adjusting for baseline GDF‐15, age, anemia, impaired renal function, history of gastrointestinal bleeding, and sex. Elevated GDF‐15 (>1800 ng/L) at 1 month was associated with an increased risk of non‐coronary artery bypass grafting‐related major bleeding (3.9% versus 1.2%; hazard ratio, 3.38; 95% CI, 1.89–6.06), independent of baseline GDF‐15. Patients who had elevated GDF‐15 levels at baseline and subsequent nonelevated GDF‐15 at 1 month had a similar risk as patients who had nonelevated levels at both measurements. Conclusions: GDF‐15 at 1 month after an ACS is related to the risk of bleeding during DAPT and provides additional information on the bleeding risk beyond baseline GDF‐15 levels. GDF‐15 levels may therefore be useful as part of decision support concerning long‐term antithrombotic treatment in patients post‐ACS.
Gesehen am 25.09.2018